Concept of a nanowire array magnetoresistance device - SHVETS, IGOR; MURPHY, SHANE; ARORA, SUNIL (My University, 2008)
We describe a concept of the magnetoresistive medium comprising of a planar array of intermingled nanowires with pinned and unpinned magnetic moments. We propose a bottom up method of forming the medium and demonstrate the feasibility of the proposed approach. We present the results of the simulations of the magnetic moments in the nanowires under an external magnetic field to illustrate the concept.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; magnetoresistive medium